1994
DOI: 10.1161/01.str.25.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Silent infarction in acute stroke patients. Prevalence, localization, risk factors, and clinical significance: the Copenhagen Stroke Study.

Abstract: Our objective was to study age-specific prevalence, computed tomographic (CT) characteristics, risk factors, and the prognostic influence on stroke outcome of silent infarction in acute stroke patients. The study was prospective and community-based and included 801 acute stroke patients, of whom 587 had first-ever stroke. A CT scan was performed in 500 (85%) of the 587 patients with first-ever stroke. CT was reviewed blindly, and infarcts were classified according to patient history as silent or symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
6

Year Published

1994
1994
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 24 publications
5
73
6
Order By: Relevance
“…19,20 Our findings differ from those reports: we found that risks of short-and long-term disability for patients with ischemic stroke with prior subclinical stroke are similar to those with prior overt stroke. On the basis of our national data, we found that subclinical stroke should be considered an important cause of functional disability in the Dependency by 2 simple questions: odds ratios calculated for dependent.…”
Section: Comparison With Previous Studiescontrasting
confidence: 99%
“…19,20 Our findings differ from those reports: we found that risks of short-and long-term disability for patients with ischemic stroke with prior subclinical stroke are similar to those with prior overt stroke. On the basis of our national data, we found that subclinical stroke should be considered an important cause of functional disability in the Dependency by 2 simple questions: odds ratios calculated for dependent.…”
Section: Comparison With Previous Studiescontrasting
confidence: 99%
“…The prevalence of silent lesions in previous CT or MRI studies varies from 10% to 47%, [6][7][8][9]23,24 and populationbased studies using MRI report a prevalence of silent lesions ranging from 11% to 28%. 2,25,26 In the present study, the prevalence of silent lesions by MRI, especially those ≥3 mm, was 44.9% in control patients, which is relatively high compared with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…From the 46 articles, 3 study populations included only type 1 diabetic patients, 2 included only type 2 diabetes, 32 were classified as "predominantly type 2 diabetes," and 9 were classified as "diabetes of unknown type" (Tables 1-3). The diagnosis of diabetes was based on history or medication use in 20 studies (7,8,14,18,20,21,24,26,28,(31)(32)(33)(37)(38)(39)(40)(41)(42)(43)(44), while in the other studies, active screening was done by fasting glucose levels, random glucose levels, or an oral glucose tolerance test. Only two studies included data on metabolic control (16,36).…”
Section: Relation Of Ct and Mri Findings To Cognition And Other Diseamentioning
confidence: 99%